Time series analysis of selected pollutants emission in the United Kingdom in years 1990-2016 - Shinkariuk, Egor; Helman, Karel; Čabla, Adam, 1985-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2019)
This bachelor thesis focuses on the analysis of four pollutants emissions in the UK in different industrial sectors. Data for this thesis were obtained from the British Office for National Statistics. The objective of the thesis is to describe the development of the harmful pollutants emissions time series in the UK in order to evaluate regulatory controls applied in this country. There are two main regulatory frameworks: the EU National Emission Ceilings Directive (NECD) (2001/81/EC) and the Gothenburg Protocol to the UNECE Convention on Long Range Transboundary Air Pollution (CLRTAP). For the mentioned evaluation, we got data for the period from 1990 to 2016.The thesis is divided into two parts. The first part is dedicated to the theoretical description of the selected statistical methods and the second part is devoted to an application of those methods on the selected time series.Tato bakalářská práce je zaměřena na analýzu časových řad emisi čtyř typů znečisťujících látek ve Velké Británii v různých sektorech průmyslu. Data pro tuto práci byla získána na webových stránkách „Office for National Statistics“.
Vedoucí práce: Karel Helman
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: statistika a ekonometrie [obor bakal. práce]; bakalářské práce; bachelor's theses